The Concept of Soft Skills Teacher Islamic Education Studies The Book 'Iẓat Al-Nasyi'īn By Sheikh Musthafa Al Ghalayani - Nadif, Achmad; Nusucha, Juli Amaliya; Rofiq, Ainur (Dirasah International Journal of Islamic Studies, 2023)
The Islamic religious education teacher is a figure of a leader who in every word or deed will be a role model for students. Departing from this, the researcher wants to analyze the book 'Idhatun Nasyi'in by Sheikh Musthafa Al- Ghalayani, because in the book the researcher finds several points as soft skills that a teacher must possess. The research approach used in this research is qualitative research. The data sources used are primary data sources and secondary data sources. Primary data sources were obtained from the book 'Iÿat Al-Nasyi'ÿn, and secondary data was obtained from the translated book 'Iÿat Al-Nasyi'ÿn, resource persons from MTS Ma'arif Kraton as well as articles, journals and websites, educational books and other relevant books. with the object discussed by the researcher. Data analysis is done by using content analysis (content analysis). There are thirteen soft skill points that must be possessed by an educator, especially for an Islamic religious educator. Among these points are intrapersonal skills which include being patient, sincere, daring to come forward, having courage, having hope, having the will, carrying out obligations, trying and trusting, and being confident. Interpersonal skills include: nationalism, the ability to lead, can be trusted and help. The concept of soft skills for Islamic education teachers contained in the book 'Iÿat Al-Nasyi'ÿn is also quite relevant in education in the current era 5.0 and appropriate when applied in learning activities at MTS Ma'arif Kraton.